2015
DOI: 10.1016/j.semarthrit.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, 6-month study of allopurinol safety in gout: The LASSO study

Abstract: This large multicenter study found that the allopurinol dose-titration strategy was well tolerated, without new safety signals emerging over 6 months. However, despite encouragement to treat to target, significant proportions of patients did not achieve target sUA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 27 publications
2
57
0
7
Order By: Relevance
“…A number of laboratory AEs were noted, in particular GGT increases. This has been reported previously2 and the clinical significance is uncertain. Minor fluctuations in creatinine resulted in a large number of creatinine CTCAE grade 1 AEs (creatinine >1–10.5× baseline).…”
Section: Discussionmentioning
confidence: 59%
“…A number of laboratory AEs were noted, in particular GGT increases. This has been reported previously2 and the clinical significance is uncertain. Minor fluctuations in creatinine resulted in a large number of creatinine CTCAE grade 1 AEs (creatinine >1–10.5× baseline).…”
Section: Discussionmentioning
confidence: 59%
“…There were more elevations in GGT and a small number of higher-grade abnormalities in the DE group compared with controls. An increase in GGT was also noted in the LASSO study 15. The clinical significance of these elevated GGTs remains unclear particularly in this group of patients with multiple comorbidities which might contribute to increases.…”
Section: Discussionmentioning
confidence: 73%
“…[1][2][3] Allopurinol is recommended as a first-line uratelowering therapy (ULT). 2 4 However, clinical trials have demonstrated that >50% of patients do not achieve sustained reductions in sUA at the most commonly used allopurinol dose of 300 mg. [5][6][7][8] Lesinurad (RDEA594) is a novel, selective uric acid reabsorption inhibitor (SURI) for treatment of gout in combination with xanthine oxidase inhibitors. Lesinurad inhibits URAT1, a uric acid transporter responsible for the reabsorption of uric acid from the renal tubular lumen.…”
Section: Introductionmentioning
confidence: 99%